Heavy-flavor production and medium properties in high-energy nuclear collisions: what next? - Aarts, Gert; Braun-Munzinger, Peter; Rothkopf, Alexander; Stachel, Johanna (The European physical journal. A, Hadrons and nuclei, 2017)
Open and hidden heavy-flavor physics in high-energy nuclear collisions are entering a new and exciting stage towards reaching a clearer understanding of the new experimental results with the possibility to link them directly to the advancement in lattice Quantum Chromo-Dynamics (QCD). Recent results from experiments and theoretical developments regarding open and hidden heavy-flavor dynamics have been debated at the Lorentz Workshop Tomography of the Quark-Gluon Plasma with Heavy Quarks, which was held in October 2016 in Leiden, The Netherlands. In this contribution, we summarize identified common understandings and developed strategies for the upcoming five years, which aim at achieving a profound knowledge of the dynamical properties of the quark-gluon plasma.